Perillaldehyde Inhibition of cGAS Reduces dsDNA-Induced Interferon Response - Chu, Lei; Li, Chenhui; Li, Yongxing; Yu, Qiuya; Yu, Huansha; Li, Chunhui; Meng, Wei; Zhu, Juanjuan; Wang, Quanyi; Wang, Chen; Cui, Shufang (Frontiers in Immunology, 2021)
Cyclic GMP-AMP synthase (cGAS), serving as a primary sensor of intracellular DNA, is essential to initiate anti-microbial innate immunity. Inappropriate activation of cGAS by self-DNA promotes severe autoinflammatory diseases such as Aicardi-Goutières syndrome (AGS); thus, inhibition of cGAS may provide therapeutic benefit in anti-autoimmunity. Here we report that perillaldehyde (PAH), a natural monoterpenoid compound derived from Perilla frutescens, suppresses cytosolic-DNA-induced innate immune responses by inhibiting cGAS activity. Mice treated with PAH are more susceptible to herpes simplex virus type 1 (HSV-1) infection. Moreover, administration with PAH markedly ameliorates self-DNA-induced autoinflammatory responses in a mouse model of AGS. Collectively, our study reveals that PAH can effectively inhibit cGAS-STING signaling and could be developed toward the treatment of cGAS-mediated autoimmune diseases.